Glutathione S-transferases of 28kDa as major vaccine candidates against schistosomiasis - Gilles Riveau (Memórias do Instituto Oswaldo Cruz., 1998)
For the development of vaccine strategies to generate efficient protection against chronic infections such as parasitic diseases, and more precisely schistosomiasis, controlling pathology could be more relevant than controlling the infection itself. Such strategies, motivated by the need for a cost-effective complement to existing control measures, should focus on parasite molecules involved in fecundity, because in metazoan parasite infections pathology is usually linked to the output of viable eggs. In numerous animal models, vaccination with glutathione S-transferases of 28kDa has been shown to generate an immune response strongly limiting the worm fecundity, in addition to the reduction of the parasite burden. Recent data on acquired immunity directed to 28GST in infected human populations, and new development to draw adapted vaccine formulations, are presented.